zmudz
  • zmudz
The roots of \(x^3 + Ax^2 + Bx + C = 0\) are the cubes of the roots of \(x^3 + x^2 - 3x -2.\) Find \(A.\)
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
If you divide \(x^3+x^2-3x-2\) by \(x+2\) you get \(x^2-x-1\), so one of the roots in -2 and you can use the quadratic formula to find the other two. Cube all three of them and substitute the cubes into \(x^3+Ax^2+Bx+C=0\). The other two roots aren't rational, so it looks like you'll end up with a pretty gnarly system of equations to solve for \(A, B,\) and \(C\). \((-2)^3 = -8\), so one of the equations is \(-512+64A-8B+C=0\)
thomas5267
  • thomas5267
\[ x^3 + x^2 - 3x -2=0\\ (x+2)\left(x^2-x-1\right)=0\\ x=-2,\,\frac{1}{2}\left(1+\sqrt{5}\right),\,\frac{1}{2}\left(1-\sqrt{5}\right)\\ r_1=\frac{1}{2}\left(1+\sqrt{5}\right)\\ r_2=\frac{1}{2}\left(1-\sqrt{5}\right) \] \[ \begin{align*} &\phantom{{}={}}\left(x-r_1^3\right)\left(x-r_2^3\right)\\ &=x^2-\left(r_1^3+r_2^3\right)x+(r_1r_2)^3\\ &=x^2-\left(\frac{1}{8}\left(1+3\sqrt{5}+15+5\sqrt{5}+1-3\sqrt{5}+15-5\sqrt{5}\right)\right)x-1\\ &=x^2-4x-1 \end{align*} \] \[ \begin{align*} &\phantom{{}={}}\left(x^2-4x-1\right)(x+8)\\ &=x^3-4x^2-x+8x^2-32x-8\\ &=x^3+4x^2-33x-8 \end{align*}\\ A=4\\ B=-33\\ C=-8 \]

Looking for something else?

Not the answer you are looking for? Search for more explanations.